2017
DOI: 10.1002/bem.22064
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to power frequency magnetic fields up to 7.6 mT: An integrated EEG/fMRI study

Abstract: We assessed the effects of power-line frequency (60 Hz in North America) magnetic fields (MF) in humans using simultaneous electroencephalography (EEG) and functional magnetic resonance imaging (fMRI). Twenty-five participants were enrolled in a pseudo-double-blind experiment involving "real" or "sham" exposure to sinusoidal 60 Hz MF exposures delivered using the gradient coil of an MRI scanner following two conditions: (i) 10 s exposures at 3 mT (10 repetitions); (ii) 2 s exposures at 7.6 mT (100 repetitions)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…They also found that theta increased in on reward signal 38 . In Julien Modolo et al, study, alpha remains unchanged at the occipital region in magnetic frequency (60 Hz) stressor 39 .…”
Section: Resultsmentioning
confidence: 88%
“…They also found that theta increased in on reward signal 38 . In Julien Modolo et al, study, alpha remains unchanged at the occipital region in magnetic frequency (60 Hz) stressor 39 .…”
Section: Resultsmentioning
confidence: 88%
“…Its purpose was to assess the change in perception when patients received more than one MRI examination. The methodology of this questionnaire was based and modified on the study of Modolo et al published in 2017 [ 26 ].…”
Section: Methodsmentioning
confidence: 99%